Perbandingan Pembelajaran Kooperatif Talking Chips Dengan Konvensional Dan Keaktifan Siswa Terhadap Hasil Belajar Ekonomi SMA N 1 Kecamatan Guguak Lima Puluh Kota - Sri Gustina Dinova; Syamwil Syamwil (Jurnal Salingka Nagari, 2023)
The purpose of this study is 1) To compare student learning outcomes in economics subjects in class XI SMA N 1 Kecamatan Guguak Lima Puluh Kota using the talking chips cooperative learning model versus the conventional model, 2) To compare the learning outcomes of students who are more active in economics subjects with students who are less active in class XI SMA N 1 Kecamatan Guguak Lima Puluh Kota, 3) To investigate the interaction of the talking chip cooperative learning model and traditional learning with activity in class XI economics subjects at SMA N 1 Kecamatan Guguak Lima Puluh Kota. This is a quasi-experimental study. Purposive sampling is a technique used in sampling. Through "two way ANOVA" analysis, both data sets were analyzed descriptively and inductively. The study's findings are as follows: 1) There are differences in student learning outcomes when using the talking chips cooperative learning model versus conventional learning models. 2) There is no difference in learning outcomes between students who are more active and students who are less active. 3) There is interaction between talking chips and traditional cooperative learning models with student activity, but it is not significant.